TANGGUNG-GUGAT CAMAT ATAS PENERBITAN SURAT KETERANGAN GANTI RUGI (SKGR) SEBAGAI DASAR PENGALIHAN KEPEMILIKAN TANAH - Devie Rachmat Ali Hasan Rifaie (Jotika English and Education Center, 2024)
One of the roles of the sub-district head is to issue a Certificate of Land Compensation (CLC) for every community who conducts buying and selling transactions on the agreed plot of land. However, a problem arose over the actions taken by the sub-district head, because there was no statutory regulation that confirmed the sub-district's authority in issuing the CLC. This study uses normative legal research because it is to see the form of void norms and legal uncertainty related to the authority of the sub-district head. The results of the research obtained that there is indeed a form of legal uncertainty over the government's actions taken by the sub-district head in issuing the CLC so that the camat always interprets the form of customary law that has been happening so far. Even the camat does not have legal protection if there is a substantive or procedural error in an CLC. In conclusion, it is necessary to issue complete and concrete laws and regulations regarding the actions of the sub-district heads so far that have issued CLC for the purposes of land administration affairs for the wider community.